Tinjauan Sistematis Pendekatan Etnosains dalam Pembelajaran Kimia untuk Meningkatkan Berpikir Kritis - Dina Puspitasari; Nazwa Altafunnisa; Sulhatul Abadiyah (Sumule Indonesia Publishing, 2025)
This study aims to systematically examine the application of the ethnoscience approach in chemistry education and its contribution to enhancing students' critical thinking skills. A Systematic Literature Review was conducted on 16 selected articles published between 2021 and 2025. The analysis reveals that integrating local wisdom into chemistry learning encourages active student engagement in understanding scientific concepts within contextual frameworks. Learning becomes more meaningful when students actively explore traditional knowledge relevant to chemical concepts. This approach has been demonstrated to enhance various aspects of critical thinking, including problem-solving skills, curiosity, and argumentative abilities. Approximately 81% of the reviewed studies reported significant improvements in students' essential thinking indicators following the implementation of the ethnoscience approach. These findings indicate that ethnoscience is an effective instructional strategy for simultaneously fostering conceptual understanding and critical thinking skills in chemistry education.